Queer Migrations : Sexuality, U.S. Citizenship, and Border Crossings. - Luibhéid, Eithne (University of Minnesota Press, 2001)
Queer Migrations brings together scholars to provide analyses of the norms, institutions, and discourses that affect queer immigrants of color, also providing ethnographic studies of how these newcomers have transformed established immigrant communities i.